Exploring Maqāṣid al-Sharīʿah in the OIC’s Role in Addressing Muslim Minority Conflicts: A Case Study of Pattani, Thailand - Suciyani, Suciyani; Mamaeng, Faisol (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examines the efforts of the Organization of Islamic Cooperation (OIC) in addressing the conflict involving Malay Muslims in Southern Thailand. As the second-largest intergovernmental organization after the United Nations, the OIC plays a critical role in safeguarding Muslim interests globally, including minority Muslim communities. Focusing on the Pattani conflict, this study analyzes the application of Maqāṣid al-Sharīʿah in the OIC's conflict resolution strategies, which include peaceful dialogue, humanitarian aid, and cultural recognition. The study employs a qualitative approach, using library research and document analysis to explore the OIC’s interventions since the conflict's escalation in 2004. Findings reveal that the OIC's diplomatic efforts have significantly contributed to peace-building initiatives in Southern Thailand, particularly through its collaboration with Malaysia as a facilitator between the Thai Government and Malay Muslim groups. Despite ongoing challenges, the OIC continues to push for dialogue and reconciliation, underscoring its commitment to protecting the cultural and human rights of the Muslim minority while respecting Thailand's sovereignty. These efforts illustrate the OIC's broader role in promoting international peace and stability.